Claire’s Anxiety Disorder and Justine’s Depression After Her Mother’s Frustration in Melancholia - Retno Ramadhina (Yayasan Baru Haji Samsudin, 2025)
The researchers selected the 2011 film Melancholia as the primary source to analyze because they found something in it that could be useful for everyone who reads this article in terms of knowledge and learning. Lars Von Trier wrote the script and also served as the director. The researches recognized that the circumstances and condition depicted in this film are identical to what occurs in modern society. The analysis of the data presented in this film is done through the use of qualitative research methodologies. Science fiction is the subject of the film. The authors employed both sociological and psychological approach to analyze the movie. Social conflict theory and social chaos theory are employed in sociological approach. While social rejection, anxiety disorders, and depression in the psychological approach. By utilizing those methods and theories, it can be deduced that Melancholia (2011) depicts the sisters' genuine struggle as they deal with a variety of mental diseases with various underlying causes while working as a team to deal with a crisis while everyone is gone